A Collection of Non-Marine Gastropods from Mangalore, Karnataka - Narasimhaiah, N.; Smitha, Ms.; Singh, Y. Tenjing (International Multidisciplinary Research Journal, 2014)
Diversity of freshwater and terrestrial gastropod molluscs from Mangalore region has studied. 12 specimens were identified up to species level except Glessula from two sites, Kadri and Jeppu Kudupady located in Mangalore. Among these 13 specimens, 3 were freshwater gastropods and 10 were terrestrial gastropods. There is always a threat to molluscs because of the rapid urbanization in Mangalore. Therefore, conservation of these species should be done to avoid the fragmentation of their habitat and not to become extinct species.